Role of cerebral angiography in vertebrobasilar occlusive disease. Issue 6 (June 1975) - Caplan, L R; Rosenbaum, A E
Abstract : The authors attempt to separate clinical subgroups of patients within the larger category of vertebrobasilar artery disease, and to indicate the present role of angiography in their recognition and management. Angiography is of use in separating posterior fossa occlusive vascular lesions from space occupying lesions. In addition, by defining the locus and nature of the occlusive process, it may result in more rational treatment and prognostication. Subgroups of vertebrobasilar ischaemia which have a favourable prognosis may be separable clinically or, in unclear cases, angiographically.